Association of ERCC2/XPD polymorphisms and the risk of head and neck carcinoma: a systematic review, meta-analysis, trial sequential analysis, network analysis, and functional effects - Mohammad Moslem Imani; Ali Ashabi; Farzad Rezaei; Atefe Saffar Shahroudi; Sadegh Kashkouli; Edris Sadeghi; Masoud Sadeghi (BMC Oral Health)
Abstract Objectives and aims The combination of genetic and environmental factors may contribute to the carcinogenesis of HNC. Despite the reported associations between xeroderma pigmentosum group D (XPD) polymorphisms and HNC, the results have been inconsistent, with different studies reporting varying results. Therefore, our aim is to assess the association of three XPD polymorphisms (rs13181, rs1799793, and rs238406) in a comprehensive meta-analysis. Materials and methods An exhaustive literature review was performed across several databases, including PubMed, Web of Science, Scopus, and Cochrane Library, up to November 18, 2023, without any restrictions. The effect sizes were presented as the odds ratio (OR) with a 95% confidence interval (CI). Results Thirty-nine articles including 56 studies were entered into the meta-analysis. Evaluating rs13181, rs1799793, and rs238406 polymorphisms in five genetic models, just significant associations were found for rs1799793 polymorphism in heterozygous and dominant models. The findings reported that the ethnicity and the cancer subtype for rs13181, the ethnicity, the sample size, and the control source for rs1799793, and the ethnicity and the control source for rs238406 polymorphisms were effective factors in the pooled results. Trial sequential analysis suggested that the studies included an insufficient number of individuals. Sensitivity analysis reported stability of pooled results. The XPD protein variants were predicted to be benign. Conclusions The study reveals a significant association between the rs1799793 polymorphism and HNC, but not rs13181 and rs238406 polymorphisms. Future studies should also aim to minimize the impact of confounding factors and heterogeneity to ensure more accurate results.